The hoax - Irving, Clifford (EBL-Schweitzer, 2014)
Cover; Author's Note; Part One; Chapter 1 - Genesis in Palma; Chapter 2 - Wife and Mistress; Chapter 3 - The Ibiza Mob; Chapter 4 - South of the Border; Part Two; Chapter 5 - Project Octavio; Chapter 6 - All Right So Far!; Chapter 7 - Helga Takes a Trip; Chapter 8 - Bonanza; Chapter 9 - ""Who's Howard Today-You or Me?""; Part Three; Chapter 10 - Bungalow One at the Beachcomber; Chapter 11 - The French Quarter; Chapter 12 - The 1,000 Letter; Chapter 13 - ""McGraw-Hill Announced Today . . .""; Chapter 14 - Confusion to Our Enemies; Chapter 15 - Confusion to Our Allies